Agenda Good Governance dan Globalisasi Ekonomi: Suatu Tinjauan Kritis - Budi Winatno (FH 2004 UMY, 2015)
As a concept, development and good governance are not neutral, but they bring domination and inlerest. Currently. in era of globalization, there is a trend that shows democratization and the agenda of good governance are suspected to become a neoliberal project armed to strengthen the domination of market over the stale. Therefore, in order to prevent the agenda of good governance serving the interest of global corporations, democracy should be able to guarantee the individual rights, and the government continuously plays its crucial role in pushing the realization of socialjustice. ln the context of maintaining democracy and civil socjety, the agenda ofgood govemance are not only implemented by public institutions, but also they are done by both global clrporations and global governance institutions.